10 Developing guidelines for opioid prescribing and adjustment in renal impairment in an acute medical admissions unit. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Howorth, Kate; Foggett, Emma; Atkinson, Jane; Henderson, Fraser; Grogan, Eleanor; Frew, Katie
Abstract : Background: Incorrect opioid prescribing can significantly impact patient care and safety, resulting in poor pain control or risk of opioid toxicity. Renal failure often means adjustment of opioid doses is needed. Local audit demonstrated incorrect prescribing in acute medical admissions, particularly in patients with renal impairment, and a survey showed low confidence amongst junior doctors in prescribing opioids. Methods: Local specific guidelines were developed for opioid prescribing and adjustment in Acute Kidney Injury (AKI) and for initiating opioids in patients with a reduced eGFR on the medical admissions unit. These were in line with the North of England Cancer Network Palliative Care Guidelines and were reviewed by the Trust's Palliative Care team. Teaching was conducted with the junior doctors working in acute medicine about the guidelines and practicing using them with example cases. Questionnaires were completed before and after the teaching to assess confidence in prescribing opioids. The guidelines were downloaded on the doctors' work phones and laminated on the wards. Results: Junior doctors were not confident in opioid prescribing and adjusting in AKI and Chronic Kidney Disease (CKD) prior to the teaching and availability of new guidelines. Confidence increased after the teaching for prescribing opioids, particularly in patients with renal impairment. For example, confidence in initiating opioids in patients with AKI was on average 5.63 out of 10 before the teaching (1 not confident and 10 very confident) and 7.93 afterwards. Conclusions: The availability of specific guidelines for prescribing and adjusting opioids in acute medical admissions for patients with renal impairment significantly increased junior doctors' confidence in this. A repeat audit will now be conducted to determine if this has impacted on the prescribing of opioids in practice. Results of this will be available at the conference.